Delineating closely related dinoflagellate lineages using phylotranscriptomics. Issue 4 (13th June 2018) - Annenkova, Nataliia V.; Ahrén, Dag; Logares, Ramiro; Kremp, Anke; Rengefors, Karin
Abstract : Recently radiated dinoflagellates Apocalathium aciculiferum (collected in Lake Erken, Sweden), Apocalathium malmogiense (Baltic Sea) and Apocalathium aff. malmogiense (Highway Lake, Antarctica) represent a lineage with an unresolved phylogeny. We determined their phylogenetic relationships using phylotranscriptomics based on 792 amino acid sequences. Our results showed that A. aciculiferum diverged from the other two closely related lineages, consistent with their different morphologies in cell size, relative cell length and presence of spines. We hypothesized that A . aff. malmogiense and A. malmogiense, which inhabit different hemispheres, are evolutionarily more closely related because they diverged from a marine common ancestor, adapting to a wide salinity range, while A. aciculiferum colonized a freshwater habitat, by acquiring adaptations to this environment, in particular, salinity intolerance. We show that phylotranscriptomics can resolve the phylogeny of recently diverged protists. This has broad relevance, given that many phytoplankton species are morphologically very similar, and single genes sometimes lack the information to determine species' relationships.